X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=advanced_topics%2Fmonads_in_category_theory.mdwn;h=173160e51c310018c87b43984820f3ffcffd176e;hp=518324244503cd52d93077d5b49db45e1f6fb59d;hb=446376aee15c6fbc9d71383d1c7654fd02ebb8f6;hpb=95e37df6ddcd64a91b2e9e49531933bad2084c7a diff --git a/advanced_topics/monads_in_category_theory.mdwn b/advanced_topics/monads_in_category_theory.mdwn index 51832424..173160e5 100644 --- a/advanced_topics/monads_in_category_theory.mdwn +++ b/advanced_topics/monads_in_category_theory.mdwn @@ -1,6 +1,3 @@ -**Don't try to read this yet!!! Many substantial edits are still in process. -Will be ready soon.** - Caveats ------- I really don't know much category theory. Just enough to put this @@ -8,11 +5,16 @@ together. Also, this really is "put together." I haven't yet found an authoritative source (that's accessible to a category theory beginner like myself) that discusses the correspondence between the category-theoretic and functional programming uses of these notions in enough detail to be sure that -none of the pieces here is misguided. In particular, it wasn't completely -obvious how to map the polymorphism on the programming theory side into the -category theory. And I'm bothered by the fact that our `<=<` operation is only -partly defined on our domain of natural transformations. But this does seem to -me to be the reasonable way to put the pieces together. We very much welcome +none of the pieces here is mistaken. +In particular, it wasn't completely obvious how to map the polymorphism on the +programming theory side into the category theory. The way I accomplished this +may be more complex than it needs to be. +Also I'm bothered by the fact that our `<=<` operation is only partly defined +on our domain of natural transformations. +There are three additional points below that I wonder whether may be too +cavalier. +But all considered, this does seem to +me to be a reasonable way to put the pieces together. We very much welcome feedback from anyone who understands these issues better, and will make corrections. @@ -51,12 +53,12 @@ To have a category, the elements and morphisms have to satisfy some constraints: (ii) composition of morphisms has to be associative - (iii) every element E of the category has to have an identity - morphism 1E, which is such that for every morphism f:C1→C2: + (iii) every element X of the category has to have an identity + morphism 1X, which is such that for every morphism f:C1→C2: 1C2 ∘ f = f = f ∘ 1C1 -These parallel the constraints for monoids. Note that there can be multiple distinct morphisms between an element `E` and itself; they need not all be identity morphisms. Indeed from (iii) it follows that each element can have only a single identity morphism. +These parallel the constraints for monoids. Note that there can be multiple distinct morphisms between an element `X` and itself; they need not all be identity morphisms. Indeed from (iii) it follows that each element can have only a single identity morphism. A good intuitive picture of a category is as a generalized directed graph, where the category elements are the graph's nodes, and there can be multiple directed edges between a given pair of nodes, and nodes can also have multiple directed edges to themselves. Morphisms correspond to directed paths of length ≥ 0 in the graph. @@ -65,14 +67,14 @@ Some examples of categories are: * Categories whose elements are sets and whose morphisms are functions between those sets. Here the source and target of a function are its domain and range, so distinct functions sharing a domain and range (e.g., `sin` and `cos`) are distinct morphisms between the same source and target elements. The identity morphism for any element/set is just the identity function for that set. -* any monoid (S,⋆,z) generates a category with a single element `x`; this `x` need not have any relation to `S`. The members of `S` play the role of *morphisms* of this category, rather than its elements. All of these morphisms are understood to map `x` to itself. The result of composing the morphism consisting of `s1` with the morphism `s2` is the morphism `s3`, where s3=s1⋆s2. The identity morphism for the (single) category element `x` is the monoid's identity `z`. +* any monoid (S,⋆,z) generates a category with a single element `Q`; this `Q` need not have any relation to `S`. The members of `S` play the role of *morphisms* of this category, rather than its elements. All of these morphisms are understood to map `Q` to itself. The result of composing the morphism consisting of `s1` with the morphism `s2` is the morphism `s3`, where s3=s1⋆s2. The identity morphism for the (single) category element `Q` is the monoid's identity `z`. -* a **preorder** is a structure (S, ≤) consisting of a reflexive, transitive, binary relation on a set `S`. It need not be connected (that is, there may be members `s1`,`s2` of `S` such that neither s1≤s2 nor s2≤s1). It need not be anti-symmetric (that is, there may be members `s1`,`s2` of `S` such that s1≤s2 and s2≤s1 but `s1` and `s2` are not identical). Some examples: +* a **preorder** is a structure (S, ≤) consisting of a reflexive, transitive, binary relation on a set `S`. It need not be connected (that is, there may be members `s1`,`s2` of `S` such that neither s1 ≤ s2 nor s2 ≤ s1). It need not be anti-symmetric (that is, there may be members `s1`,`s2` of `S` such that s1 ≤ s2 and s2 ≤ s1 but `s1` and `s2` are not identical). Some examples: * sentences ordered by logical implication ("p and p" implies and is implied by "p", but these sentences are not identical; so this illustrates a pre-order without anti-symmetry) * sets ordered by size (this illustrates it too) - Any pre-order (S,≤) generates a category whose elements are the members of `S` and which has only a single morphism between any two elements `s1` and `s2`, iff s1≤s2. + Any pre-order (S,≤) generates a category whose elements are the members of `S` and which has only a single morphism between any two elements `s1` and `s2`, iff s1 ≤ s2. Functors @@ -229,12 +231,12 @@ If φ is a natural transformation from `F` to `M(1C)` and
 	γ = (φ G')
 	  = ((unit <=< φ) G')
+	  since unit is a natural transformation to M(1C), this is:
 	  = (((join 1C) -v- (M unit) -v- φ) G')
 	  = (((join 1C) G') -v- ((M unit) G') -v- (φ G'))
 	  = ((join (1C G')) -v- (M (unit G')) -v- γ)
 	  = ((join G') -v- (M (unit G')) -v- γ)
-	  since (unit G') is a natural transformation to MG',
-	  this satisfies the definition for <=<:
+	  since (unit G') is a natural transformation to MG', this is:
 	  = (unit G') <=< γ
 
@@ -245,11 +247,11 @@ Similarly, if ρ is a natural transformation from `1C` to `MR'`,
 	γ = (ρ G)
 	  = ((ρ <=< unit) G)
+	  = since ρ is a natural transformation to MR', this is:
 	  = (((join R') -v- (M ρ) -v- unit) G)
 	  = (((join R') G) -v- ((M ρ) G) -v- (unit G))
 	  = ((join (R'G)) -v- (M (ρ G)) -v- (unit G))
-	  since γ = (ρ G) is a natural transformation to MR'G,
-	  this satisfies the definition <=<:
+	  since γ = (ρ G) is a natural transformation to MR'G, this is:
 	  = γ <=< (unit G)
 
@@ -265,10 +267,10 @@ Summarizing then, the monad laws can be expressed as: (ii) (ρ <=< γ) <=< φ = ρ <=< (γ <=< φ) (iii.1) (unit G') <=< γ = γ - when γ is a natural transformation from some FG' to MG' + whenever γ is a natural transformation from some FG' to MG' (iii.2) γ = γ <=< (unit G) - when γ is a natural transformation from G to some MR'G + whenever γ is a natural transformation from G to some MR'G @@ -282,7 +284,7 @@ In category theory, the monad laws are usually stated in terms of `unit` and `jo P3. functors "preserve identity", that is for every element C1 in F's source category: F(1C1) = 1F(C1). --> -Let's remind ourselves of some principles: +Let's remind ourselves of principles stated above: * composition of morphisms, functors, and natural compositions is associative @@ -290,9 +292,9 @@ Let's remind ourselves of some principles: * if η is a natural transformation from `G` to `H`, then for every f:C1→C2 in `G` and `H`'s source category C: η[C2] ∘ G(f) = H(f) ∘ η[C1]. -* (η F)[E] = η[F(E)] +* (η F)[X] = η[F(X)] -* (K η)[E} = K(η[E]) +* (K η)[X] = K(η[X]) * ((φ -v- η) F) = ((φ F) -v- (η F)) @@ -388,9 +390,9 @@ Finally, we substitute ((join G') -v- (M γ) -v- φ) for (i') ((join G') (M γ) φ) etc are also in T + - - +
 	    (ii) (ρ <=< γ) <=< φ  =  ρ <=< (γ <=< φ)
 	==>
 		     (ρ <=< γ) is a transformation from G to MR', so
@@ -409,45 +411,57 @@ Finally, we substitute ((join G') -v- (M γ) -v- φ) for 
 
-
-
+
 	 (iii.1) (unit G') <=< γ  =  γ
 	         when γ is a natural transformation from some FG' to MG'
 	==>
 			 (unit G') is a transformation from G' to MG', so:
-			 (unit G') <=< γ becomes: ((join G') (M unit G') γ)
+			 (unit G') <=< γ becomes: ((join G') (M (unit G')) γ)
+			                      which is: ((join G') ((M unit) G') γ)
 
 			 substituting in (iii.1), we get:
-			 ((join G') (M unit G') γ) = γ
+			 ((join G') ((M unit) G') γ) = γ
 
-			 which will be true for all γ just in case:
-	         ((join G') (M unit G')) = the identity transformation, for any G'
-
-			 which will in turn be true just in case:
-	(iii.1') (join (M unit) = the identity transformation
+			 which is:
+			 (((join (M unit)) G') γ) = γ
 
+			 [-- Are the next two steps too cavalier? --]
 
+			 which will be true for all γ just in case:
+			 for any G', ((join (M unit)) G') = the identity transformation
 
+			 which will in turn be true just in case:
+	(iii.1') (join (M unit)) = the identity transformation
+
+
 	 (iii.2) γ  =  γ <=< (unit G)
 	         when γ is a natural transformation from G to some MR'G
 	==>
-			 unit <=< γ becomes: ((join R'G) (M γ) unit)
+			 γ <=< (unit G) becomes: ((join R'G) (M γ) (unit G))
 			
 			 substituting in (iii.2), we get:
 			 γ = ((join R'G) (M γ) (unit G))
 		
 			 which by lemma 2, yields:
-			 γ = ((join R'G) ((unit MR'G) γ)
+			 γ = (((join R'G) ((unit MR'G) γ)
+
+			 which is:
+			 γ = (((join (unit M)) R'G) γ)
+
+			 [-- Are the next two steps too cavalier? --]
 
 			  which will be true for all γ just in case:
-	         ((join R'G) (unit MR'G)) = the identity transformation, for any R'G
+			 for any R'G, ((join (unit M)) R'G) = the identity transformation
 
 			 which will in turn be true just in case:
 	(iii.2') (join (unit M)) = the identity transformation
@@ -483,25 +497,20 @@ The base category C will have types as elements, and monadic functions as
 A monad `M` will consist of a mapping from types `'t` to types `M('t)`, and a mapping from functions f:C1→C2 to functions M(f):M(C1)→M(C2). This is also known as liftM f for `M`, and is pronounced "function f lifted into the monad M." For example, where `M` is the list monad, `M` maps every type `'t` into the type `'t list`, and maps every function f:x→y into the function that maps `[x1,x2...]` to `[y1,y2,...]`.
 
 
-In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
-
-A "monadic value" is any member of a type M('t), for any type 't. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (φ : F('t) → M(F'('t))) to an argument `a` of type `F('t)`.
-
+In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad."
 
-Let `'t` be a type variable, and `F` and `F'` be functors, and let `phi` be a polymorphic function that takes arguments of type `F('t)` and yields results of type `MF'('t)` in the monad `M`. An example with `M` being the list monad:
+A "monadic value" is any member of a type `M('t)`, for any type `'t`. For example, any `int list` is a monadic value for the list monad. We can think of these monadic values as the result of applying some function `phi`, whose type is `F('t)->M(F'('t))`. `'t` here is any collection of free type variables, and `F('t)` and `F'('t)` are types parameterized on `'t`. An example, with `M` being the list monad, `'t` being `('t1,'t2)`, `F('t1,'t2)` being `char * 't1 * 't2`, and `F'('t1,'t2)` being `int * 't1 * 't2`:
 
 
 	let phi = fun ((_:char, x y) -> [(1,x,y),(2,x,y)]
 
-Here phi is defined when `'t = 't1*'t2`, `F('t1*'t2) = char * 't1 * 't2`, and `F'('t1 * 't2) = int * 't1 * 't2`. -Now where `gamma` is another function into monad `M` of type F'('t) → MG'('t), we define: +Now where `gamma` is another function of type F'('t) → M(G'('t)), we define:
 	gamma =<< phi a  =def. ((join G') -v- (M gamma)) (phi a)
-
 	                 = ((join G') -v- (M gamma) -v- phi) a
 					 = (gamma <=< phi) a
 
@@ -518,59 +527,59 @@ With these definitions, our monadic laws become:
-	Where phi is a polymorphic function from type F('t) -> M F'('t)
-	and gamma is a polymorphic function from type G('t) -> M G' ('t)
-	and rho is a polymorphic function from type R('t) -> M R' ('t)
+	Where phi is a polymorphic function of type F('t) -> M(F'('t))
+	gamma is a polymorphic function of type G('t) -> M(G'('t))
+	rho is a polymorphic function of type R('t) -> M(R'('t))
 	and F' = G and G' = R, 
-	and a ranges over values of type F('t) for some type 't,
-	and b ranges over values of type G('t):
+	and a ranges over values of type F('t),
+	b ranges over values of type G('t),
+	and c ranges over values of type G'('t):
 
 	      (i) γ <=< φ is defined,
 			  and is a natural transformation from F to MG'
 	==>
 		(i'') fun a -> gamma =<< phi a is defined,
-			  and is a function from type F('t) -> M G' ('t)
-
-
+			  and is a function from type F('t) -> M(G'('t))
+
+
 	     (ii) (ρ <=< γ) <=< φ  =  ρ <=< (γ <=< φ)
 	==>
 			  (fun a -> (rho <=< gamma) =<< phi a)  =  (fun a -> rho =<< (gamma <=< phi) a)
 			  (fun a -> (fun b -> rho =<< gamma b) =<< phi a)  =  (fun a -> rho =<< (gamma =<< phi a))
 
 	   (ii'') (fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)
+
- - +
 	  (iii.1) (unit G') <=< γ  =  γ
 	          when γ is a natural transformation from some FG' to MG'
-
+	==>
 			  (unit G') <=< gamma  =  gamma
-			  when gamma is a function of type FQ'('t) -> M G'('t)
+			  when gamma is a function of type F(G'('t)) -> M(G'('t))
 
 			  fun b -> (unit G') =<< gamma b  =  gamma
 
 			  (unit G') =<< gamma b  =  gamma b
 
-			  As below, return will map arguments c of type G'('t)
-			  to the monadic value (unit G') b, of type M G'('t).
+			  Let return be a polymorphic function mapping arguments of any
+			  type 't to M('t). In particular, it maps arguments c of type
+			  G'('t) to the monadic value (unit G') c, of type M(G'('t)).
 
 	(iii.1'') return =<< gamma b  =  gamma b
+
- - +
 	  (iii.2) γ  =  γ <=< (unit G)
 	          when γ is a natural transformation from G to some MR'G
 	==>
 			  gamma  =  gamma <=< (unit G)
-			  when gamma is a function of type G('t) -> M R' G('t)
+			  when gamma is a function of type G('t) -> M(R'(G('t)))
 
-			  gamma  =  fun b -> gamma =<< ((unit G) b)
+			  gamma  =  fun b -> gamma =<< (unit G) b
 
-			  Let return be a polymorphic function mapping arguments
-			  of any type 't to M('t). In particular, it maps arguments
-			  b of type G('t) to the monadic value (unit G) b, of
-			  type M G('t).
+			  As above, return will map arguments b of type G('t) to the
+			  monadic value (unit G) b, of type M(G('t)).
 
 			  gamma  =  fun b -> gamma =<< return b
 
@@ -588,7 +597,7 @@ Summarizing (ii''), (iii.1''), (iii.2''), these are the monadic laws as usually
 
 *	`return =<< gamma b  =  gamma b`
 
-	Usually written reversed, and with `u` standing in for `phi a`:
+	Usually written reversed, and with `u` standing in for `gamma b`:
 
 	`u >>= return  =  u`
 
@@ -596,6 +605,6 @@ Summarizing (ii''), (iii.1''), (iii.2''), these are the monadic laws as usually
 
 	Usually written reversed:
 
-	return b >>= gamma  =  gamma b
+	`return b >>= gamma  =  gamma b`